Advocating synergising a critical dialogic approach with competencies-trained dialoguing with GenAI tools to enhance students’ critical thinking and communication competencies - Rahimi, Muhammad (Journal of University Teaching and Learning Practice, 2025)
This paper proposes synergising a critical dialogic approach with competencies-trained dialoguing with GenAI tools like ChatGPT as multidisciplinary more knowledgeable others to enhance students’ critical thinking and professional communication competencies. It emphasises the importance of engaging all students, regardless of their learning profiles, in authentic dialogic interactions requiring higher-order thinking skills to develop and enhance their critical thinking and communication competencies. It suggests that students develop at least a fundamental level of the target competencies through the critical dialogic approach and apply them in dialoguing with GenAI tools to further enhance their developing competencies. This paper also discusses the potential issues with the accuracy and reliability of ChatGPT’s responses and the importance of critical thinking and communication competencies in dialoguing with GenAI tools. Moreover, this paper proposes a professional proposal competencies framework, along with an associated rubric and key guiding questions, for use in the dialogic teaching and learning of critical thinking and communication competencies, dialoguing with GenAI tools to enhance these competencies, and assessing them. Overall, this paper conceptualises GenAI tools as additional more knowledgeable multidisciplinary dialoguing partners for students to enhance their developing competencies through critical dialoguing and proposes that the future of education may depend on our ability to synergise human and artificial intelligence to create more engaging and effective learning approaches.